The Evaluation of Dana Desa in Monitoring the Management (The Study of The Role of Badan Permusyawatan Desa In Garung Village, SubDistrict Sambeng, Lamongan Regency) - Yohanes Fritantus (Asia Pacific Journal of Management and Education (APJME), 2019)
The aim of this research is to analyze the role of Badan Permusyawaratan Desa in monitoring the management of Dana Desa and analyze the obstacle that faced by the Badan Permusyawaratan Desa (BPD) in village Garung, Sub-District Sambeng, District Lamongan. The research method used guidance with interview, observation and documentary. The results of the study that the role of the Badan Permusyawaratan Desa (BPD) in overseeing the management of Dana Desa is divided into each process, namely the Planning stage, Implementation, and reporting. Constraints faced include, the absence of a work program, inadequate measurement of performance, no corrective action taken to prevent irregularities repeatedly. In addition to the three aspects above, the findings in this study, there are aspects that most contribute to the role of the Badan Permusyawaratan Desa in overseeing the management of Dana Desa, namely human competence (HR), budget, facilities and infrastructure, and work methods of the organization.